Topology and analysis of an N-stage cascaded polymer eight-port microring optical router with 7N channel wavelengths - 李翠婷 郑玲娇 郑悦 郑传涛 (Optoelectronics letters, 2015)
Eight-port optical routers are widely used in cluster-mesh photonic networks-on-chip（No C）. By using 24 groups of cross-coupling two-ring resonators, a 1-stage 8-port polymer optical router is proposed, which can optically route 7 channel wavelength data streams along definite path in two-dimensional（2D） plane. Under the selected 7 channel wavelengths, the insertion losses along all routing paths are within 0.02-0.58 d B, the maximum crosstalk of all routing operations is less than-39 d B, and the device footprint size is about 0.79 mm2. Then, a universal novel structure and routing scheme of N-stage cascaded 8-port optical router are presented, which contains 7N channel wavelengths. Because of the good scalability in wavelength, this device shows potential application of wideband signal routing in optical No C.